Lesley Chamberlain: The Food and Cooking of Russia - D, P (Petits Propos Culinaires, 2024)
Lesley Chamberlain: The Food and Cooking of Russia: Allen Lane, London 1982: 330 pages, some period black and white illustrations, hardcover, £9.95.